Development of Pisa Model Math Problems with Central Java Cultural Context - Catur Yustika Melati; Heri Retnowati (Ridwan Institute, 2023)
This research aims to develop PISA model mathematics questions with a Central Javanese cultural context that are valid, reliable and have a potential effect on students' mathematical literacy abilities. The research method used in this research is design research type development studies, which consists of two stages: preliminary and formative evaluation. The resulting test instrument was then validated by experts consisting of experienced Mathematics Education lecturers and Mathematics Teachers. The respondents in this research were 29 students at SMP IT Harapan Ummat Purbalingga. The product of this research is PISA model Mathematics test questions with a Central Javanese cultural context that are valid, reliable and have a potential effect on students' literacy abilities based on the PISA framework. The validation results were analyzed using the Aiken V index by calculating the correlation coefficient ( ) and the Aiken V coefficient value was between 0.583 to 0.917, which means that for all questions, 4 questions had high criteria and 3 questions had medium criteria. Then reliability was analyzed using IBM SPSS Statistics 2022 by determining the Cronbach Alpha coefficient and obtained a value of 0.904. Then, from the results of the analysis at the field test stage, it can be seen that several basic mathematical abilities are emerging which are based on mathematical literacy abilities such as reasoning and argumentation abilities of 44.3%, communication skills of 34%, representation abilities of 41.25%, ability to formulate strategies to solve problems. Problems amounted to 70.3%, the ability to use symbolic language, formats, and techniques and operations amounted to 57.67%, and the ability to use mathematical tools amounted to 23.5%.